Efeito da variação das propriedades ácidas do catalisador sobre o processo de desidratação catalítica do glicerol em fase gás - Júnior, Moacir José da Silva (2019)
In the dehydration of the glycerol investigation with the goal of yield acetol and acrolein, were synthetized oxide containing alumina within support and above it, different salts of oxide within of Sb, W, Nb, Ce. Above this was addiction the oxide of copper. The materials synthesis was do two paths. Via Pechini and wet impregnation, with the target of to compare the methods. Then all solids were characterized by XRD, BET, TPR, SEM, TG and Pyridine Adsorption. Subsequently all materials were submitted the test catalytic. The materials prepared by web impregnation showed high activity and the catalyst of niobium (conversion remained stable) and cerium (conversion showed decreased with time) if showed more efficient (conversion above 80%) in the test with time of 5 hours and solution of glycerol 10%wt. Materials containing W were active (conversion above 80%) with exception of the W/Al, however showed decrease of the activity with the time. For most solids the acetol was the major yield. Highlighted the solids containing Sb presented very low catalytic activity (conversion below 10%). This were submitted the test of ethanol dehydration forward a better know of the weak acidic. Eventually, oxides were characterized after the test catalytic forward best understand of the results obtained.